The 'Auto-Mapic' map of Great Britain - O'Loughlin, Thomas (Charles Close Society for the Study of Ordnance Survey Maps, 2015)
A study of a mechanical road atlas from the 1960s which is compared with codex form 'glove box' atlases from the period